Complicated grief after suicide bereavement and other causes of death. Issue 5 (28th May 2017) - Tal, Ilanit; Mauro, Christine; Reynolds, Charles F.; Shear, M. Katherine; Simon, Naomi; Lebowitz, Barry; Skritskaya, Natalia; Wang, Yuanjia; Qiu, Xin; Iglewicz, Alana; Glorioso, Danielle; Avanzino, Julie; et al.
ABSTRACT: The authors compared baseline demographic characteristics, clinical features, and grief-related thoughts, feelings, and behaviors of individuals bereaved by suicide, accident/homicide and natural causes participating in a complicated grief (CG) treatment clinical trial. Severity of CG and depression and current depression diagnosis did not vary by loss type. After adjusting for baseline demographic features, time since death and relationship to the deceased, those with CG after suicide had the highest rates of lifetime depression, preloss passive suicidal ideation, self-blaming thoughts, and impaired work and social adjustment. Even among this treatment-seeking sample of research participants with CG, suicide survivors may face unique challenges.